STRUCTURED INVESTMENT PRODUCTS – IS CAPITAL PROTECTION WORTH ITS COST? - Purovirta, Samu (My University, 2016)
Structured products and their performance have not been studied a lot by academics. Some studies state that the pricing of them is beneficial for the bank and rational investor should put their money in other instruments. This study examines the performance of a few different structured products strategies and compares the return characteristics to another form of passive investing – index investing, as well as to a form of active indexing – a dynamic portfolio of actively managed mutual funds. The structured product strategies all have been given a different risk/reward profile to see if capital protection, partial capital protection or no capital protection are good alternative investment instruments. The study is conducted on equity investments in Europe during the euro era 1999-2015. The results show that during the turbulent period the portfolio of actively managed mutual funds is the best performing strategy. Fully capital protected and non-capital protected strategies are next best depending on which metrics are used. Flooring the losses is also a decent strategy, but the lower the floor and the riskier the product, the less attractive the strategy becomes.
Keywords: Structured product; capital protection; active investing vs. passive investing; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|